An Emerging Mineral‐Based Dielectric Material: Intrinsic Dielectric Properties and Modulated. (20th September 2022) - Liang, Xiaozheng; Xie, Weimin; Ren, Yangjun; Yang, Huaming
Abstract: High energy density polymer nanocomposites reinforced with high dielectric constant ferroelectric nanoparticles exhibit great potential for energy storage applications in modern electronic and electrical systems. However, further improvements in the U e of polymer nanocomposites with a higher breakdown strength ( E b ) is of utmost importance. Tuning the permittivity from the filler center to the surrounding matrix in composites can alleviate local charge concentrations. Here, a gradient dielectric constant buffer layer is constructed via induced selectively titanium dioxide is inserted into the multilayer aluminosilicate. This gradient‐structured buffer layer remarkably weakened the charge density around the ferroelectric particles, which gave rise to high breakdown strength and increased the energy density of the polymer nanocomposites. Furthermore, the density functional theory (DFT) calculation reveals an active charge transfer between buffer layer and poly(vinylidene fluoride‐co‐hexafluoropropylene). The space charge density distribution is simulated via finite element methods to verify the experimental dielectric breakdown results in the nanocomposite films. Therefore, this work provides a new strategy to balance the coupling relationship between energy density and breakdown strength. Abstract : A gradient dielectric constant buffer layer constructed by induced selectivity inserting titanium dioxide into multilayer aluminosilicate is developed. This gradient‐structured buffer layer remarkably weakened the charge density around ferroelectric particles, which give rise to high breakdown strength and much‐promoted energy density of polymer nanocomposites.